Entropic entanglement criteria for Fermion systems - Zander, Claudia (2012)
Entanglement criteria for general (pure or mixed) states of systems consisting of two; identical fermions are introduced. These criteria are based on appropriate inequalities; involving the entropy of the global density matrix describing the total system, on the one; hand, and the entropy of the one-particle reduced density matrix, on the other hand. A; majorization-related relation between these two density matrices is obtained, leading to a; family of entanglement criteria based on Renyi’s entropic measure. These criteria are; applied to various illustrative examples of parametrized families of mixed states. The; dependence of the entanglement detection efficiency on Renyi’s entropic parameter is; investigated. The extension of these criteria to systems of N identical; fermions is also considered.